Inhibidores naturales y de síntesis sobre la brotación de tubérculos de papa (Solanum tuberosum) variedad cecilia - Carrillo Freire, Guido Alfredo (2009)
The present research had by objective to determine the influence of natural inhibitors and synthesis about budding of potato tubers (Solanum tuberosum) Cecilia variety. The used bioregulators were mesocarpio walnut extract in dilutions of 1:1, 1:5 and 1:10; and, clorocolina chloride in dose of 1.500 p.p.m., 2.000 p.p.m. and 2.500 p.p.m. The researched work was carried out in Patate canton, main parish, Tungurahua province, in liquors factory “Blacksmithing”. The laboratory analyses were carried out under induced conditions in a gauged freezer to 50C, 60-70% of relative humidity and 0 luminosity. The experimental employed design was a D.B.C.A. with 7 treatments and 5 repetitions, the data taking was made during 40 days, which were carried out the statistical analysis by means of Statistical Analysis System (SAS). The procedure ANOVA was used for the variance analysis. Tukey test (0.05) for comparison of measures CORR, for correlations among study variables. It was also carried out an economic analysis of application costs from each treatment to 1 ton of potato tubers. From the results it provides the best treatment is the application of chlorocholine chloride to 2.500 p.p.m. it slows the sprouting of potato tubers variety Cecilia in 38,8 days, treatment T4 (walnut fruit extract 1:1) is that presented the biggest cost in conservation Cecilia potato variety in the use of inhibitors and T1 C.C.C. (chlorocholine chloride 1,500 p.p.m.) had the lowest cost. To store potato tubers Cecilia variety it is recommended to use clorocolina chloride in dose of 2.500 p.p.m. in a temperature of 50C, 60-70% of relative humidity and 0 luminosity.